733 Long-Term Outcomes of Outpatient Laser Ablation for Recurrent Non-Muscle Invasive Bladder Cancer: A Retrospective Cohort Study. (12th October 2021) - Grover, S; Raj, S; Russell, B; Thomas, K; Nair, R; Thurairaja, R; Khan, M S; Malde, S
Abstract: Aim: Non-muscle-invasive bladder cancer (NMIBC) is the most prevalent form of bladder cancer, predominantly affecting the elderly population. The most common treatment for recurrent NMIBC is transurethral resection of the bladder tumour (TURBT), which carries a risk of perioperative morbidity and mortality in this often-co-morbid population. Outpatient laser ablation of low-grade NMIBC recurrences is a minimally invasive treatment option, but long-term efficacy is poorly reported. Method: We retrospectively reviewed the case notes of all patients treated with Holmium:YAG laser ablation from 2008-2016. Data regarding patient demographics, original histology, dates of procedures, follow-up time, recurrence, progression, and complications were recorded. Results: A total of 199 procedures were performed on 97 patients (mean age of 83.56), 73 (75.3%) of which originally had low-grade (G1 or G2) tumours. Overall, 55 (56.7%) patients developed tumour recurrence at long-term follow-up (mean 5.36 years), and only 9 (9.3%) patients had tumour progression to a higher stage or grade, but there was no progression to muscle-invasive disease. The median recurrence-free, progression-free and overall survival times were 1.69 years (95% CI 1.20-2.25), 5.70 years (95% CI 4.10-7.60) and 7.60 years (95% CI 4.90-8.70), respectively. No patients required emergency inpatient admission after laser ablation for any associated complications. Conclusions: Office-based Holmium: YAG laser ablation is an oncologically-safe method of managing recurrent low-grade non-muscle-invasive bladder cancer in the long-term, with no patients progressing to muscle-invasive disease. Furthermore, the procedure is safe, and no significant complications were seen in this elderly and co-morbid population.